Primordial purity : oral instructions on the three words that strike the vital point - Rinpoche, Dilgo Khyentse (Halifax : Vajra Vairochana Translation Committee, 1999)
The path of trekchö is the way of directly and thoroughly cutting through the misconceptions of samsara to lay bare the primordial purity of the nature of mind. This powerful practice is illuminated by Dilgo Khyentse Rinpoche in his commentary on an essential text based on the atiyoga dzogchen instructions of the outstanding nineteenth-century master Patrul Rinpoche. Three Words That Strike the Vital Point is the famous seminal statement by Garap Dorje that is said to encapsulate all the myriad dzogchen tantras. The key instructions on it by Patrul Rinpoche--the verses known as "The Special Teaching of Khepa Shri Gyalpo"--Form the basis for the discourse in Primordial Purity. It explains that in dzogchen, when one has fully recognized that all the confusion of samsara is the expressive power of great emptiness, confusion is spontaneously liberated into the primordial purity of mind's essential nature. Compassion spontaneously arises, accomplishing the benefit of sentient beings. Dilgo Khyentse Rinpoche illuminates this beautifully in this profound work, which will inspire students of Buddhism and deepen their experiential appreciation of the teachings
Keywords: RELIGION -- Buddhism -- Rituals & Practice